2010
DOI: 10.1051/0004-6361/201014616
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared properties of submillimeter and optically faint radio galaxies

Abstract: We use deep observations obtained with the Photodetector Array Camera and Spectrometer (PACS) onboard the Herschel Space Observatory to study the far-infrared (FIR) properties of submillimeter and optically faint radio galaxies (SMGs and OFRGs). From literature we compiled a sample of 35 securely identified SMGs and nine OFRGs located in the GOODS-N and the A2218 fields. This sample is cross-matched with our PACS 100 μm and 160 μm multi-wavelength catalogs based on sources-extraction using prior detections at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 32 publications
13
82
5
Order By: Relevance
“…However, we can see that our sample is systematically biased towards colder dust temperatures when compared to the local L IR – T D relationship (Chapman et al 2003). This bias towards colder dust temperatures for submm/mm‐selected samples is now well established (Chapman et al 2010; Magdis et al 2010; Magnelli et al 2010).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, we can see that our sample is systematically biased towards colder dust temperatures when compared to the local L IR – T D relationship (Chapman et al 2003). This bias towards colder dust temperatures for submm/mm‐selected samples is now well established (Chapman et al 2010; Magdis et al 2010; Magnelli et al 2010).…”
Section: Resultsmentioning
confidence: 79%
“…Kovács et al 2006), allowing us to characterize their IR luminosity ( L IR ) and dust temperature ( T D ) with unprecedented accuracy (e.g. Chapman et al 2010; Magnelli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al (2004a) summarizes the results of the first search of the warm-dust analogue of SMGs as Optically Faint Radio Galaxies (OFRGs). OFRGs later became known as Submillimeter-Faint Radio Galaxies (SFRGs) in later work (Casey et al, 2009c,a;Magnelli et al, 2010;Casey et al, 2011b) which confirmed that they were truly warm-dust analogues of SMGs with similar physical properties. Figure 8 illustrates the submillimeter dust-temperature selection effect another way.…”
Section: Intrinsic Variation In Sedsmentioning
confidence: 94%
“…It is noteworthy that some confirmed ULIRGs at z ∼ 2 have hotter spectral energy distribution (SED) shapes, resulting in 850‐μm fluxes lying below the sensitivities of current surveys, and the high‐redshift ULIRG population could be up to twice as large as implied by 850‐μm surveys alone (Chapman et al ; Casey et al ; Magdis et al ). These galaxies which have been missed by 850‐μm surveys have been detected by BLAST (Casey et al ) and Herschel (Magnelli et al ; Chapman et al ), and confirmed as ‘SMGs' with 250–500 μm flux densities still implying ULIRG‐like luminosities. The intense SFRs (∼1000 M ⊙ yr −1 ) and large molecular gas reservoirs (∼10 11 M ⊙ ; Greve et al ; Bothwell et al ) inferred for the SMGs means that they could build a stellar mass of 10 11 M ⊙ in just 100 Myr.…”
Section: Introductionmentioning
confidence: 97%